On the relationship between income poverty and multidimensional poverty in China - Wang, X; Feng, H; Xia, Q; Alkire, S (Oxford Poverty and Human Development Initiative (OPHI), 2016)
This paper attempts to examine the theoretical relationship between income poverty and multidimensional poverty, and to explore the empirical linkages and discrepancies between these two types of poverty using the Alkire-Foster (AF) multidimensional poverty measurement method with 2011 China Health and Nutrition Survey (CHNS) data. Regarding the relationship between income poverty and multidimensional poverty, poverty can be summarized as not the mere lack of income but the deprivation of human basic capability, covering both monetary and non-monetary poverty. The statistical analysis on income poverty and multidimensional poverty measurement shows that the coincidence of income poverty and multidimensional poverty is 31%. In other words, 69% of multidimensionally poor households are not considered poor in terms of income poverty. The econometric results indicate that an increase in income can significantly reduce the incidence of multidimensional poverty in each dimension, but the impact is limited.